INtrinsic Capacity and its RElAtionship With Life-SpacE Mobility (INCREASE): a cross-sectional study of community-dwelling older adults in Singapore - Yee Sien Ng; Yew Yoong Ding; Jia Qi Lee; Aisyah Latib; Laura Tay (BMJ Open)
Objectives To examine the association of intrinsic capacity (IC) with life-space mobility (LSM) among community-dwelling older adults and to determine whether age and gender modify this relationship.Design Cross-sectional study.Setting Public housing blocks, senior activity centres and community centres in the Northeastern region of Singapore.Participants 751 community-dwelling older adults aged ≥55 years old and able to ambulate independently with or without walking aid.Primary and secondary outcome measures IC and LSM. Standardised IC factor scores were calculated through confirmatory factor analysis using variables representing the five IC domains cognition, locomotion, sensory, vitality and psychological. LSM was measured using the University of Alabama at Birmingham Study of Aging Life-Space Assessment instrument. Association of IC with LSM and its effect modification by age and gender were examined with regression analyses.Results The participants had a mean age of 67.6 and mean LSM score of 88.6. IC showed a positive and significant association with LSM (β=6.33; 95% CI=4.94 to 7.72) and the effect remained significant even after controlling for potential confounders (β=4.76; 95% CI=3.22 to 6.29), with p<0.001 for both. Age and gender did not demonstrate significant modification on this relationship.Conclusions Our findings support the empirical rigour of the International Classification of Functioning, Disability and Health framework, which suggests that IC influences the extent to which a person participates in the community. Our findings also provide guidance for healthcare providers who aim to enhance LSM and promote healthy ageing in older adults.